Efektivitas Pelayanan Administrasi di Kantor Desa Ilomta Kecamatan Bulango Ulu - Irawati Yohan; Yacob Noho Nani; Sri Yulianty Mozin (Transbahasa, 2025)
Effectiveness of Administrative Services at the Ilomata Village Office, Bulango Ulu District, using three indicators used in service procedures that have been in accordance with standards, but their implementation still faces obstacles. Timeliness is not optimal due to delays in officers, power outages and limited facilities. Accuracy or precision in document preparation is also still lacking, marked by errors in writing data, these errors cause public dissatisfaction because they have to go back and forth to the Village Office to make improvements. On the other hand, the style of service delivery is considered good because the officers are polite and communicative, and the service procedures are easy to understand and do not burden the community. This study shows that Administrative Services at the Ilomata Village Office are not yet fully effective. Timeliness is not optimal due to delays in officers and minimal facilities and accuracy of service is also still lacking due to errors in writing without verification. However, the style of service delivery is good and in accordance with village apparatus procedures and is considered communicative by the community.